Antioxidant and Antiplatelet Activities in Extracts from Green and Fully Ripe Tomato Fruits (Solanum lycopersicum) and Pomace from Industrial Tomato Processing. (17th February 2013) - Fuentes, Eduardo; Carle, Reinhold; Astudillo, Luis; Guzmán, Luis; Gutiérrez, Margarita; Carrasco, Gilda; Palomo, Iván
Abstract : The consumption of fruits and vegetables is accepted to be one of the strategies to reduce risk factors for these diseases. The aim of this study was to examine potential relationships between the antioxidant and the antiplatelet activities in green mature and fully ripe (red) tomatoes and of lycopene-rich byproducts of tomato paste processing such as pomace. The total phenol content of tomato components was the highest in peels, pulp, and in the mucilaginous myxotesta covering the tomato seeds with values 36.9 ± 0.8, 33.3 ± 0 0.5, and 17.6 ± 0.9  mg GAE/100 g, respectively (P < 0.05 ). Tomato peels had the highest antioxidant activity, both, as measured by the FRAP (46.9 ± 0.9   μ mol Fe +2 /g, P < 0.05 ) and the DPPH assays (97.4 ± 0.2 %, 1000  μ g/mL, P < 0.05 ). Pomace extracts showed the highest antiplatelet activity induced by ADP, collagen, TRAP-6, and arachidonic acid. While the maturation stage of the tomato fruit affected the antioxidant effect, antiplatelet activity was independent of fruit ripeness. Finally, based on the present results, tomato and its byproducts may be considered as a valuable source of antioxidant and antiplatelet activities.